2023
DOI: 10.3390/ijerph20054506
|View full text |Cite
|
Sign up to set email alerts
|

Physical Impact of SARS-CoV-2 Infection in a Population of Italian Healthcare Workers

Abstract: SARS-CoV-2 infection often causes symptoms and illness that can last for months after the acute phase, i.e., so-called “Long COVID” or Post-acute COVID-19. Due to the high prevalence of SARS-CoV-2 infection among Healthcare Workers (HCWs), post-COVID-19 symptoms can be common and threaten workers’ occupational health and healthcare systems’ functioning. The aim of this cross-sectional, observational study was to present data related to post-COVID-19 outcomes in a population of HCWs infected by COVID-19 from Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
1
0
1
Order By: Relevance
“…Our results are consistent with those of the literature, which showed that fatigue is the most frequent symptom after SARS-CoV-2 infections [18]. Lulli et al identified that over half of healthcare workers infected with COVID-19 mentioned at least one symptom persisting, and fatigue was the most reported disorder [19]. According to a systematic review, fatigue affects more than 50% of patients [20].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with those of the literature, which showed that fatigue is the most frequent symptom after SARS-CoV-2 infections [18]. Lulli et al identified that over half of healthcare workers infected with COVID-19 mentioned at least one symptom persisting, and fatigue was the most reported disorder [19]. According to a systematic review, fatigue affects more than 50% of patients [20].…”
Section: Discussionsupporting
confidence: 92%
“…These symptoms included fatigue, difficulties with concentration, respiratory problems, and a poor quality of life. More than half of the population analyzed in an Italian study of healthcare professionals (56.3%) displayed persistent symptoms, the most common of which was fatigue (32.1%), followed by musculoskeletal pain (13.6%) and dyspnea (13.2%); these symptoms restricted the employees' working conditions 46 . According to a study of the general population in several nations, more than 54.6% of people reported long periods of being unable to work; 34.5% of people reported losing their jobs due to illness; 63.9% reported having trouble coping with daily tasks; and 17.6% reported having financial difficulties as a result of the disease.…”
Section: Covid-19 Long-term Impacts On Workers' Healthmentioning
confidence: 99%
“…La evaluación de numerosos trabajadores en el ámbito del servicio social en Alemania identificó que casi el 73% experimentó síntomas persistentes durante más de tres meses, destacándose la fatiga, problemas de concentración y dificultades para respirar, además de una baja calidad de vida en aquellos trabajadores con síntomas persistentes 45 . Una investigación con trabajadores de la salud en Italia reflejó que más de la mitad de la población analizada (56,3%) manifestaron síntomas persistentes, entre los que se destacan la fatiga con el 32,1%, seguido de dolores musculoesqueléticos con el 13,6% y la disnea con el 13,2%; síntomas que limitaron las condiciones laborales de esta población de trabajadores 46 . Por su parte, un estudio con población general de varios países destacó que más del 54,6% de las personas experimentaron largos períodos sin poder trabajar, el 34,5% habían perdido su trabajo debido a una enfermedad, el 63,9% informaron dificultades para hacer frente a las actividades cotidianas, y el 17,6% había experimentado dificultades financieras como resultado de la enfermedad.…”
Section: Impactos a Largo Plazo Por Covid-19 En La Salud De Los Traba...unclassified